2004
DOI: 10.1097/01.phm.0000137315.17214.93
|View full text |Cite
|
Sign up to set email alerts
|

Time Course of Recovery of Juvenile Skeletal Muscle After Botulinum Toxin A Injection

Abstract: Our findings provide scientific evidence to support the clinical situation in which the interinjection interval of 3-6 mos of botulinum toxin A at a similar dosage is used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
77
0
1

Year Published

2006
2006
2011
2011

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 72 publications
(84 citation statements)
references
References 32 publications
6
77
0
1
Order By: Relevance
“…Doses administered in this study fall within clinical recommendations and were previously demonstrated to be effective in the mouse, rat, and rabbit. 8,12,19,20 The results demonstrate a dosedependent response to BoNTA injection and that injection volume plays a critical role in determining the efficacy of a particular dose.…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations
“…Doses administered in this study fall within clinical recommendations and were previously demonstrated to be effective in the mouse, rat, and rabbit. 8,12,19,20 The results demonstrate a dosedependent response to BoNTA injection and that injection volume plays a critical role in determining the efficacy of a particular dose.…”
Section: Discussionmentioning
confidence: 86%
“…19 Although histology may confirm the morphometric changes in the atrophied muscle and its neuromuscular junctions, alterations in neuromuscular junction remodeling, and muscle recovery are already well documented. 1,5,12,13,15,16,19,34,35 This study explores functional outcomes after varying injection dose and volume, and recognizes that it is limited to MFG testing, EMG testing, and muscle mass.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For a limb skeletal muscle, the lateral gastrocnemius was selected because it is composed largely of fast muscle fiber types (Armstrong and Phelps, 1984), which is similar to the high percent of fast muscle fiber types found in extraocular muscle. The lateral gastrocnemius muscle can be easily stimulated in situ with wire electrodes in contact with the lateral tibial nerve and has been used frequently for in situ contractile studies (Ameredes and Provenzano, 1997;Grassi et al, 2002;de Haan, 1998;Ma et al, 2004).…”
Section: Surgical Preparation Of Animalsmentioning
confidence: 99%